Rhino horn use by consumers of traditional Chinese medicine in China. Issue 5 (23rd February 2021) - Cheung, Hubert; Mazerolle, Lorraine; Possingham, Hugh P.; Biggs, Duan
Abstract: The medicinal use of rhino horn in Asia is a major driver of poaching and illegal trade. Research into the different actors involved in this trade is needed to inform policymaking and improve conservation outcomes. While researchers have investigated rhino horn consumers in Vietnam, studies have yet to focus on China. Here, we conducted a large‐scale online survey to investigate medicinal rhino horn consumption in China's Guangdong province. One in seven respondents reported having used rhino horn in the past year. These individuals tended to be older, male, wealthier and better educated; several healthcare usage variables were also associated with rhino horn consumption. These findings can help guide the development of tailored demand reduction interventions. Our results question the effectiveness of the global community's current approach to rhino conservation. We conclude by highlighting the need for conservationists to work more closely with key stakeholders to find lasting and sustainable solutions.